The association of factor V G1961A (factor V Leiden), prothrombin G20210A, MTHFR C677T and PAI-1 4G/5G polymorphisms with recurrent pregnancy loss in Bosnian women - Amela Jusić; Devleta Balić; Aldijana Avdić; Maja Pođanin; Adem Balić (Medicinski glasnik, 2018)
Aim: To investigate association of factor V Leiden, prothrombin G20210A, MTHFR C677T and PAI-1 4G/5G polymorphisms with recurrent pregnancy loss in Bosnian women. Methods: A total of 60 women with two or more consecutive miscarriages before 20 weeks of gestation with the same partners and without history of known causes or recurrent pregnancy loss were included. A control group included 80 healthy women who had one or more successful pregnancies without history of any complication which could be associated with miscarriages. Genotyping of factor V Leiden, prothrombin G20210A, MTHFR C677T and PAI-1 4G/5G polymorphisms were performed by polymerase chain reaction/restriction fragments length polymorphism method (PCR/RFLP). Results: Both factor V Leiden and MTHFR C677T polymorphisms were significantly associated with recurrent pregnancy loss (RPL) in Bosnian women while prothrombin G20210A and PAI-1 4G/5G polymorphisms did not show strongly significant association. Conclusion: The presence of thrombophilic polymorphisms may predispose women to recurrent pregnancy loss. Future investigation should be addressed in order to find when carriers of those mutations, polymorphisms should be treated with anticoagulant therapy.
Keywords: thrombophilia; habitual abortions; gene polymorphisms